2012
DOI: 10.1097/ana.0b013e318254fb70
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Intraoperative Hypotension During Craniotomy for Traumatic Brain Injury

Abstract: Background Hypotension after traumatic brain injury (TBI) is associated with poor outcomes. However, data on intraoperative hypotension (IH) are scarce and the effect of anesthetic agents on IH is unknown. We examined the prevalence and risk factors for IH, including the effect of anesthetic agents during emergent craniotomy for isolated TBI. Methods A retrospective cohort study of patients ≥ 18 years who underwent emergent craniotomy for TBI at Harborview Medical Center (level-1 trauma center) between Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 25 publications
4
22
0
Order By: Relevance
“…Unlike Townsend et al 11 who recommended delaying surgery to prevent secondary insults including hypotension, similar to our results, Velhamos et al 12 and Kalb et al 14 reported no difference in intraoperative hypotension based on timing of orthopedic surgery. Interestingly, the prevalence of intraoperative hypotension in this series is similar to the 65% prevalence we recently reported during craniotomy for TBI 9 indicating that hypotension is a common problem, irrespective of the type of surgery in TBI patients. Avoidance of hypotension may be crucial even in patients undergoing surgery days after TBI because cerebral autoregulation may be impaired up to 2 weeks after moderate-severe TBI, 33 predisposing them to the risk of cerebral ischemia.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Unlike Townsend et al 11 who recommended delaying surgery to prevent secondary insults including hypotension, similar to our results, Velhamos et al 12 and Kalb et al 14 reported no difference in intraoperative hypotension based on timing of orthopedic surgery. Interestingly, the prevalence of intraoperative hypotension in this series is similar to the 65% prevalence we recently reported during craniotomy for TBI 9 indicating that hypotension is a common problem, irrespective of the type of surgery in TBI patients. Avoidance of hypotension may be crucial even in patients undergoing surgery days after TBI because cerebral autoregulation may be impaired up to 2 weeks after moderate-severe TBI, 33 predisposing them to the risk of cerebral ischemia.…”
Section: Discussionsupporting
confidence: 87%
“…25,26 In addition, surgical intervention leads to fluid shifts and blood loss. Secondary insults during craniotomy for TBI have been reported, 9,10,2732 and as evidenced by our data here, secondary insults are also common during orthopedic surgery in patients with TBI and may contribute to worse outcomes. Therefore, anesthesiologists can potentially contribute to improving TBI outcomes by reducing the burden of secondary insults during craniotomy as well as extracranial surgery.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…45 Moreover, the presence of multiple CT lesions, subdural hematoma, maximum thickness of CT lesion and longer duration of anesthesia increase the risk for intraoperative hypotension, and anesthesiologists can use the presence of these factors to anticipate and expediently address these complications. 46 Perioperative hypotension should be treated promptly. Warm, non-glucose containing isotonic crystalloid solution is preferable for intravenous administration in TBI patients.…”
Section: Intravenous Fluids Blood Pressure Management and Vasopressomentioning
confidence: 99%